The Correlation between Awareness, Motivation, and Perception with Safe Behavior at Ngadiredjo Sugar Factory - Charisma Agustin; Endang Dwiyanti (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: Sugar Factory (PG) Ngadiredjo is one of the manufacturing industry sectors where there are various stages of the production to process sugarcane into white crystal sugar. One of the risks of accidents in each production process is due to worker behavior. This study aims to analyze the strength of the correlation between awareness, motivation, and perception with safe behavior in engineering and processing section workers at PG Ngadiredjo Kediri. Methods: This research was an observational study with a cross-sectional approach. The sample of this study was 80 workers who were determined using the total population technique. Data collection techniques used questionnaires and safe behavior observations. The data obtained were analyzed descriptively using cross-tabulation and the Spearman correlation statistical test to determine the strength of the correlation between independent and dependent variables. Results: The results showed that most workers aged â‰¥ 36 years (42.5%), had a good level of awareness, good motivation, and fair perceptions. In addition, the results showed a strong correlation between awareness and perception with safe behavior and a very strong correlation between motivation and safe behavior. Conclusion: Based on the research results, there is a strong correlation between awareness and perception with safe behavior and a very strong correlation between motivation and safe behavior. The level of awareness, motivation, and perceptions of a worker will directly influence the level of his safe behavior.